Towards the enantioselective synthesis of anti-HIV agents litseaverticillols C and K from D-glucose - Mohapatra, Debendra K.; Mondal, Dhananjoy; Guriar, Mukund K. (Tetrahedron, 2007)
The first enantioselective synthesis towards the litseaverticillols C and K has been achieved, from D-glucose, using the ring closing metathesis (RCM) and Wittig reactions as key steps. (c) 2007 Elsevier Ltd. All rights reserved.